2019
DOI: 10.1016/j.neucom.2018.06.081
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the most informative features using a structurally interacting elastic net

Abstract: Feature selection can efficiently identify the most informative features with respect to the target feature used in training. However, state-of-the-art vector-based methods are unable to encapsulate the relationships between feature samples into the feature selection process, thus leading to significant information loss. To address this problem, we propose a new graph-based structurally interacting elastic net method for feature selection. Specifically, we commence by constructing feature graphs that can incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
(74 reference statements)
0
21
0
Order By: Relevance
“…It is also shown that AEN-CMI contributes to the adaptive clustering effect by assessing the significance of gene ranking. Lixin Cui and Yue Wang [15] suggested a technique that can encapsulate the structural correlation between feature methods in the feature selection process, and display features in the form of graphics and vertices. Therefore, the obtained information matrix is utilised to produce an optimization model to determine the object with the greatest relevance and least redundancy to the objective function.…”
Section: Related Workmentioning
confidence: 99%
“…It is also shown that AEN-CMI contributes to the adaptive clustering effect by assessing the significance of gene ranking. Lixin Cui and Yue Wang [15] suggested a technique that can encapsulate the structural correlation between feature methods in the feature selection process, and display features in the form of graphics and vertices. Therefore, the obtained information matrix is utilised to produce an optimization model to determine the object with the greatest relevance and least redundancy to the objective function.…”
Section: Related Workmentioning
confidence: 99%
“…Although Lasso has been proved to be easily interpretable and effective under various circumstances, it still has some shortcomings [18]. Zou and Hastie [19] put forward an expansion approach called elastic net to conduct selection.…”
Section: Adaptive Elastic Net-based Feature Selectionmentioning
confidence: 99%
“…Neighbor Embedding (NE) approaches assume that features which are drawn from small low-and high-resolution patches lie on two local geometrically similar manifolds (Wang et al, 2019;Bai et al, 2014Bai et al, , 2018. Based on this assumption NE approaches reconstruct high-resolution features with local geometric structure recording coefficients which are shared in lowresolution space (Liu and Bai, 2012;Cui et al, 2017Cui et al, , 2019. A representative NE approach is A+ method proposed by Timofte et al (Timofte et al, 2014).…”
Section: Related Workmentioning
confidence: 99%